Export promotion in least developed countries: an overview of programs, challenges and prospects - Selassie, Habte G. (Henry Stewart Talks, 2009)
Export promotional activities of national governments, NGOs and international institutions, Developed countries' programs for promoting exports from least developed countries (LDCs), Outsourcing agricultural production to LDCs, Effectiveness of export promotion initiatives, Challenges and prospects for export development in LDCs